Technical Alienation in Contemporary Global Sculpture - Khawla Ghadban Obaid (Basrah Arts Journal, 2024)
The research was concerned with studying technical alienation in contemporary global sculpture, as alienation is a concept that gained an important place due to its connection with humans and then moved to different fields, including art. Accordingly, the study was built on four chapters. The first chapter included: the research problem that ended with the following question (What are the uses of technical alienation in contemporary global sculpture)? It also included the importance of research and the need for it, as well as the goal of the research and the limits of the research, and then defining the terms mentioned in the title and defining them linguistically, terminologically and procedurally. As for the second chapter: it included two sections: The first section: by studying the concept of alienation in philosophical thought and what its manifestations are. The second section: was concerned with studying the representations of alienation in contemporary global sculpture. The chapter concluded by reviewing the indicators of the theoretical framework to benefit from them in analyzing the research sample. As for the third section: it included the research community. His sample, the research tool. The fourth chapter: included the results of the research, its discussion, and its conclusions. Among the results reached by the researcher are: 1. The phenomenon of alienation reflected different states of representation depending on the level of alienation, its time, and its social place that did not belong to its paths. It constituted a realistic (material) representation of the sculptor’s state of separation from the surroundings of his community, embodied in the sculptural treatments of his works. 2. The state of alienation for the sculptor was represented by an internal struggle between two active tendencies, the first represented by his desires, while the second was founded on his needs that could not be satisfied, in order to contribute to a creative, sculptural product to bring them out (the state of alienation). Therefore, the state of alienation is considered a type of active orientation (alienation). Positive) It resulted in sculptural works with a creative path.